2018
DOI: 10.3233/nre-172298
|View full text |Cite
|
Sign up to set email alerts
|

Concussion and the autonomic nervous system: An introduction to the field and the results of a systematic review

Abstract: BACKGROUND:Recent evidence suggests that autonomic nervous dysfunction may be one of many potential factors contributing to persisting post-concussion symptoms.OBJECTIVE:This is the first systematic review to explore the impact of concussion on multiple aspects of autonomic nervous system functioning.METHODS:The methods employed are in compliance with the American Academy of Neurology (AAN) and PRISMA standards. Embase, MEDLINE, PsychINFO, and Science Citation Index literature searches were performed using rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 219 publications
(321 reference statements)
1
44
0
1
Order By: Relevance
“…There were no side effects and the patient has remained free of concussion related symptoms for the past 8 years. The ART testing was consistent with the presence of an IF in the head which is consistent with current thinking about the pathophysiology of concussions . The ART testing was consistent with a brain localization IF as a result of the patient's head trauma with consequent increased irritability, crying, and lack of full, alert eye contact.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…There were no side effects and the patient has remained free of concussion related symptoms for the past 8 years. The ART testing was consistent with the presence of an IF in the head which is consistent with current thinking about the pathophysiology of concussions . The ART testing was consistent with a brain localization IF as a result of the patient's head trauma with consequent increased irritability, crying, and lack of full, alert eye contact.…”
Section: Discussionsupporting
confidence: 80%
“…Irritability and visual system changes can present in the context of concussion . The autonomic nervous system and neuronal depolarization appear to be involved in concussion pathophysiology …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autonomic nervous system (ANS) dysfunction has been recognized as a marker of post-concussion syndrome. 2 In recent literature, disruption of heart rate variability (HRV) has been shown to be a measurable aspect of this dysfunction. 3,4 Although these studies have shown a disruption in HRV, 5 no study to date has continuously monitored HRV in athletes pre-and post-SRC.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major challenges in dealing with PCS is categorizing the underlying pathologies and understanding their effect on the symptomatology, to which the evidence suggests a multitude of neurophysiological and psychosomatic mechanisms. These mechanisms include disruptions in cerebral blood flow (CBF), 23,24 changes in brain metabolism, 25 axon damage, 26 changes in autonomic and neuroendocrine function, [27][28][29][30] cervical injury and postural weakness, 31 disturbances in the vestibular and oculomotor system, 32,33 and neuropsychological dysfunctions. 34,35 These myriad of components and overlapping comorbidities adds to the complexity of PCS, and highlights the difficulties of having a single treatment regimen.…”
Section: Introductionmentioning
confidence: 99%